Successful Cryopreservation of Fibroblasts by DMSO Concentration Decreasing and Nanocrystalline Cerium Dioxide Adding - Polivanova , Olena; Bobrova , Olena; Sidorenko, Olga; Falko , Oksana; Chyzhevskyi , Viktor (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 285